STABILITY OF BETACYANIN PIGMENTS FROM RED PURPLE PITAYA FRUIT (Hylocereus polyrhizus) : INFLUENCE OF PH, TEMPERATURE, METAL IONS AND ASCORBIC ACID - Tang, C.S Tang, C.S; Norziah M.H Norziah M.H (Universitas Gadjah Mada, 2007)
Betacyanin pigments from red-purple pitaya fruit (Hylocereus polyrhizus) could be an attractive source of red colourant for food application. This paper presents results on the extraction of betacyanin pigments from pitaya fruits grown locally in Malaysia. Both the flesh of the fruit and its mesocarp were investigated and it was found that the flesh had higher pigment contents compared to its peel component. The concentration of betacyanins expressed as betanin equivalents per 100 g of flesh and peel were 10.1 ± 0.6 mg and 6.7 ± 0.2 mg, respectively when 80% methanol was used. The stability of betacyanin pigments were investigated at different pH, temperature and in presence of different concentrations of metal ions (Cu2+ and Fe2+) and ascorbic acid. The results showed that the pigment was most stable at pH range between 5 and 6. However, it forfeited its stability to the heat induced at elevated temperatures. Metal ions (Cu2+ and Fe2+) proved to be capable of accelerating betacyanin degradation, with Cu2+ exhibiting the greatest effect. By contrast, supplementation with ascorbic acid could enhance the pigment stability against the detrimental effects caused by pH, temperature and metal ions. Nevertheless, if the concentration of ascorbic acid exceeds 0.7 %, it may change its role from pigment stabilizer to become a pro-oxidant.